Incident factors in Andalusian university dropout: A qualitative approach from the perspective of higher education students - Santos-Villalba, María Jesús; Alcalá del Olmo Fernández, María José; Montenegro Rueda, Marta; Fernández Cerero, José (Frontiers in Education, 2023)
University dropout is currently one of the main challenges facing government bodies and state and regional universities. Both personal and institutional reasons can be identified as the root of university dropout. On a personal level, students accumulate experiences of academic failure that lead them to reflect on the possibility of continuing their studies, while from an institutional point of view, failure can be attributed to the educational deficits, reputation, and quality parameters of the university institution itself. Even though more and more universities have educational policies aimed at reducing dropout rates, the dropout figures continue to rise, which shows that this is a complex problem due to the number of variables involved. The main objective of this study is to analyse the factors influencing university dropout among Andalusian students. The methodology is qualitative through a focus group with the participation of 12 students who dropped out of their academic studies in education science degrees at the University of Malaga (Spain). The study population corresponds to students who formalised their enrolment in the first year of the degree in the 2021/22 academic year. The content analysis followed a deductive category development model. The results reveal that the factors that explain the educational abandonment of the students who are the object of this research are identification with studies that did not meet their initial expectations, the use of traditionalist methodologies, the development of a work activity and the economic difficulties in covering the costs derived from university education. The main conclusions include the importance of designing educational policies in line with the reality and needs of the students, the use of innovative methodologies that increase the degree of motivation of the students, as well as studying dropout from a holistic perspective, taking into account the multiple variables that influence its origin.